Do handgrip strength and dexterity predict respiratory function in neuromuscular disease? - Safran, Ertugrul; Ozer, Aysel Yildiz; Gurses, Hulya Nilgun (Arquivos de Neuro-Psiquiatria, 2022)
Background Neuromuscular diseases are acquired or inherited diseases that affect the function of the muscles in our body, including respiratory muscles.Objective We aimed to discover more cost-effective and practical tools to predict respiratory function status, which causes serious problems with patients with neuromuscular disease.Methods The Vignos and Brooke Upper Extremity Functional Scales were used to evaluate functional status for patient recruitment. The handgrip strength and dexterity of patients were measured using a dynamometer and nine-hole peg test. Respiratory function parameters: forced vital capacity, forced expiratory volume in one second, and peak expiratory flow were evaluated using spirometry.Results The mean age of the 30 patients was 11.5 ± 3.79 years old. Significant relationships were found between nine-hole-peg-test scores and respiratory function parameters on both sides. Significant correlations were found between both handgrip strength and respiratory function parameters (p < 0.05). In the linear regression analysis, it was seen that the forced expiratory volume in 1 second, and peak expiratory flow values could be explained in different percentages (p < 0.05).Conclusions Handgrip strength and dexterity measurements can be used as indicators for estimating respiratory function parameters in terms of cost and accessibility, although it is known that they will not replace respiratory function tests.
Keywords: Neuromuscular Diseases; Motor Skills; Respiratory Function Tests; Hand Strength